The Great Resignation: Reimagining Work and the Future of HR - Suprayitno, Degdo (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The phenomenon of "The Great Resignation" has prompted organizations to evaluate their work flexibility policies to address changing workforce needs and expectations. In this systematic review, researchers explore the role of work flexibility policies in the face of "The Great Resignation" and its implications for human resource management (HRM) and organizational culture. Researchers investigated findings from related literature published in the reputable international journal Scopus to gain insight into how work flexibility policies are understood, adopted and implemented by organizations in various contexts. The results show that work flexibility policies have a significant impact in increasing job satisfaction, employee well-being and productivity. However, challenges in performance management and effective communication were also identified. The implications of these findings reinforce the importance for organizations to adopt work flexibility policies that suit employee needs and expectations, as well as overcome emerging challenges through effective management strategies.